Caracterização do efeito antinociceptivo e anti-inflamatório do polissacarídeo extraído da levedura Kluyveromyces marxianus - Oliveira, Renata Freitas de Araujo (2015)
The yeasts produce different types of metabolites and macromolecules with huge biotechnological potential. Among them, the Kluyveromyces marxianus, species attracts industrial and economic interests for presenting certain qualities, such as thermal tolerance, high growth rates, broad substrate spectrum and modulation of immune response. This work investigated the effects of treatment with the polysaccharide extracted from the Kluyveromyces marxianus yeast (poly322) in pain and inflammation experimental models. The poly322 pharmacological properties were evaluated with writhing, formalin, nociception (manifested by CFA), tail flick, hot-plate and paw edema tests. The cytokine levels were determined by ELISA and the effects on motor performance were evaluated by rotarod and open field tests. The pretreatment with poly322 resulted in reduced nociception induced by acetic acid, CFA and formalin (late phase). Furthermore, animals treated with poly322 exhibited a significant reduction in mechanical hypernociception, paw edema, and local IL-6 levels increase induced by carrageenan. In contrast, treatment with poly322 did not alter the thermal stimulus response threshold in the tail flick and hot plate tests, indicating no central action. Confirming the specificity of the action suggested by nociceptive tests, the treatment with poly322 did not induce motor impairment. These results demonstrate that the poly322 has a potent antinociceptive and anti-inflammatory effects, possibly mediated by the inhibition of the production and/or release of the IL-6 cytokine.